ANALISIS EFISIENSI, EFEKTIVITAS SERTA KONTRIBUSI RETRIBUSI PASAR SUDAN RAYA TERHADAP TOTAL RETRIBUSI PASAR KABUPATEN TANAH BUMBU TAHUN 2018-2022 - Lutfi, Nada; Rasidah, Rasidah; Chairina, Chairina; Suhaili, Achmad (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
Regional revenue heavily relies on taxes and levies, with market levies being a significant source of income. Therefore, the government must optimize revenue from market levies. This study aims to assess the efficiency, effectiveness, and contribution of the Sudan Raya market service levies to the total market service levies in Tanah Bumbu Regency from 2018 to 2022. This research employs quantitative data with a descriptive analytical approach. The analysis utilizes formulas to evaluate the efficiency, effectiveness, and contribution of market levies based on data from 2018 to 2022. The results indicate that the efficiency level of the Sudan Raya market levy collection from 2018 to 2022 is categorized as highly efficient, with an average efficiency rate of 6.72%. The effectiveness level of the market levy collection during this period is considered effective, with an average effectiveness rate of 100.67%. Additionally, the contribution of the Sudan Raya market levies to the total market levies in Tanah Bumbu Regency from 2018 to 2022 is very substantial, with an average contribution rate of 50.53%.